Residual stump cancer of the uterine cervix - Tregear C., Horacio (2015)
We have studied the casuistry of Hospital Workers (14 years), the Pavilion V 2nd room Loayza Hospital (9) and the National Institute of Neoplastic Diseases (10 years). We found that the ratio of uterine cervical cancer and various ginecopatías is 3.14% in the Worker H. and H. 3.20% in Loayza. Not consign the Institute of Neoplastic Diseases not know the number of different ginecópatas met, what will be grounds for immediate investigation expansion study. From obtained similar figures, it could be accepted as final in our country, that for every 100 ginecópatas, 3 are carriers of uterine cervical cancer. The residual cervical stump cancer has decreased from 1.3% to 0.78% at the Institute of Neoplastic Diseases, like living in the V Hall 2 of the H. Loayza has dropped from 1% to 0.78%. In the H. Workers, it is the first study on the subject, so we have no comparison factor, but highlight is its low average of 0.39%. We advocate a greater tendency towards total hysterectomy as a means to reduce the incidence of uterine cervical cancer, leaving the subtotals for cases in which the total is contraindicated, after exhaustive study of the cervical pathology. Promote among general surgeons, limiting its tendency to practice subtotal hysterectomy.